ANALYSIS OF COCA COLA’S ADVERTISING BASED ON FERDINAND DE SAUSSURE’S SEMIOTIC STUDY - Yackie (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2025)
Semiotics is a scientific discipline that examines signs and the meanings embedded within them. In the context of mass communication, advertising serves as a medium for delivering messages to a broad audience. However, not all messages conveyed in advertisements can be easily understood by viewers. This study aims to uncover the meanings of messages contained in several Coca-Cola soft drink advertisements through a semiotic analysis. The research employs a qualitative approach with data collected through documentation and observation of selected advertisement materials. The findings show that some advertisements present meanings that are direct and easy to interpret, such as Coca-Cola with Ice and Coca-Cola with Smile, which highlight themes of freshness and joy. Meanwhile, other advertisements require deeper interpretation, such as Ice with Friend, Stories with Coca-Cola, and Taste the Feeling, as these involve more complex symbolism and emotional narratives related to social bonding and shared experiences. Overall, it can be concluded that the Coca-Cola advertisements consistently construct an image of Coca-Cola as a refreshing cold beverage that can be enjoyed at any moment in life, particularly in the presence of friends and loved ones.